Perancangan Aplikasi E-Voting Dalam Pemilihan Ketua OSIM Menggunakan PHP/MySQL Di MTsN 1 Kota Payakumbuh - Melani Silvia; Hari Antoni Musril; Darul Ilmi; Sarwo Derta (Journal of Innovative and Creativity, 2026)
The election of the OSIM President at MTsN 1 Kota Payakumbuh is still conducted using a conventional system, which presents several drawbacks, including slow vote counting, vulnerability to fraud, and high operational costs. To address these challenges, this study developed a web-based e-voting application using PHP and MySQL, aiming to improve efficiency, accuracy, transparency, and ease of use in the election process. The development followed the Research and Development (R&D) methodology to produce and evaluate the product’s effectiveness, employing the Rapid Application Development (RAD) model consisting of requirement planning, system design, and implementation stages. Product evaluation was carried out using the ISO/IEC 25010 standard, which assessed functional suitability, compatibility, and usability, alongside linguistic and design validity tests. The results showed that the functional suitability and compatibility tests both achieved a score of 100% with an “excellent” rating, while the usability test yielded 94.20%, classified as “highly feasible.” The product validity test obtained a perfect score of 1.00, confirming that the application is valid. These findings indicate that the proposed e-voting system offers a modern, effective, and reliable solution for the OSIM President election.